2016
DOI: 10.4103/ipj.ipj_67_16
|View full text |Cite
|
Sign up to set email alerts
|

“One level more:” A narrative review on internet gaming disorder

Abstract: Due to explosive growth in technology and internet usage in the last few years, internet gaming disorder (IGD) has manifested as rapidly growing public health problem mainly affecting the teen and preteen population worldwide. It has a negative impact upon physical, psychological, social, and occupational functioning of the affected individual, often leading to severe consequences. It was only recently that it has been recognized as a separate diagnosable disorder in the Diagnostic and Statistical Manual of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…The prevalence of internet gaming disorder varies worldwide and is estimated to be between 0.2% and 8.5%. 15 The present study revealed a similar finding of prevalence of problematic online gaming of 8% among the undergraduate medical students of Goa medical college. It also revealed that higher proportion of male study participants (12.1%) showed problematic online gaming than female study participants (4.9%), which is consistent with the findings of Chih-Hung Ko et al and Wartber et al 16,17 As much as 21.6% (n=54) of the study participants used internet for more than 5 hours per day which explains the high penetration of internet in daily routine of these adolescents.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of internet gaming disorder varies worldwide and is estimated to be between 0.2% and 8.5%. 15 The present study revealed a similar finding of prevalence of problematic online gaming of 8% among the undergraduate medical students of Goa medical college. It also revealed that higher proportion of male study participants (12.1%) showed problematic online gaming than female study participants (4.9%), which is consistent with the findings of Chih-Hung Ko et al and Wartber et al 16,17 As much as 21.6% (n=54) of the study participants used internet for more than 5 hours per day which explains the high penetration of internet in daily routine of these adolescents.…”
Section: Discussionsupporting
confidence: 86%
“…This is a timely inclusion because online gaming is a rapidly growing and popular industry, as evidenced by the reported revenue of over $100 billion (US) generated worldwide in 2017 (Batchelor, 2018). With increased use and popularity of online gaming, there is an increased risk of developing problematic online gaming and gaming disorder for a small minority of individuals (Naskar et al 2016). This should be of concern to the general psychiatrist who may face the increasing likelihood of individuals presenting with gaming problems in both adolescent and adult settings.…”
Section: Introductionmentioning
confidence: 99%
“…IGD has become a significant public health problem in some Asian countries due to its increasing prevalence and negative impact on mental health. [14][15][16][17] Approximately 7.4% of South Koreans aged 20-40 years were estimated to be at risk for IGD based on the DSM-5 criteria. 18 Overall socioeconomic costs in South Korea due to Internet addiction (IA), including pathological online gaming, were estimated to be in the range of 1.5-4.5 billion US dollars in 2009.…”
Section: Introductionmentioning
confidence: 99%